The Sign Language Learning in Deaf Student and Special Education Teacher in Integration Program of Hearing Problem - Mohd Hanafi Mohd Yasin; Mohd Mokhtar Tahar; Safani Bari; Faten Nazren Manaf (Department of Special Education, 2017)
This study aims to identify how to learn sign language by deaf students and the level of mastery of sign language by students and teacher of the deaf at a state school in Melaka. In addition, this research would also like to know the major obstacles faced by deaf students and teachers who learn sign language. The instrument that is used in this study is a questionnaire. The respondents contain 50 deaf students and 10 special education teacher of the deaf. Research instrument contains 4 main parts: demographic, the level of mastery of sign language, way to learn sign language and the challenges and obstacles encountered during the study of sign language. Research findings are analyzed using Statistical Package for the Social Science (SPSS) version 22.0 involving the use of descriptive statistics such as frequency, percentage and mean. Research findings indicate that the level of mastery of sign language for problematic pupils hearing and special education teachers is at mid-level. They completely use (KTBM) Kode Tangan Bahasa Melayu (Hand Code of Malay Language) in their daily teaching and communication. In addition, the way to learn sign language for deaf student is through the book while special education teachers also learn it through colleagues. The research also found that challenges as well as the obstacles often encountered to learn sign language for deaf students and special education teachers of the deaf are lack of source reference book of sign language. It is suggested that reference materials such as book and ICT are augmented in all integration program and special education of the deaf